Photo-repairable carbon dot reinforced bio-based elastomer
By using palm oil-based materials and bio-based carbon dots, a photorepairable bio-based elastomer was prepared, which solved the problems of poor mechanical properties of traditional bio-based elastomers and high energy consumption, and achieved efficient and environmentally friendly photorepair performance.
Patent Information
- Application Number
- CN202411876656.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-07
AI Technical Summary
The mechanical properties of existing bio-based elastomers are poor and cannot be repaired by photocuring, and the traditional thermal repair method consumes high energy and has degraded performance.
Palm oil fatty acid acrylamide ethyl ester is used as raw material, and hydroxyethyl acrylate and acryloyloxyethyl trimethyl ammonium chloride are comonomers. Bio-based elastomers are prepared through photocuring technology, and bio-based carbon dot enhancement is given to them.
Improve the mechanical properties and toughness of bio-based elastomers, and achieve rapid repair of damage through light repair, reducing energy consumption and maintaining performance.
Smart Images

Figure CN119569942A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of bio-based nanomaterials and bio-based elastomers, and specifically relates to a photorepairable carbon dot-reinforced bio-based elastomer. Background Art
[0002] Compared with traditional petroleum-based elastomers, bio-based elastomers have attracted attention due to their advantages of being green and environmentally friendly and having abundant raw material sources. At present, bio-based elastomers are mainly prepared from lignin, cellulose, starch and vegetable oils. Palm oil is the largest vegetable oil in terms of production, consumption and international trade in the world. It is renewable, abundant in resources and low in cost, and has good commercial prospects in bio-based resins and composite materials.
[0003] Elastomers are inevitably damaged during use. The traditional repair technology for elastomers is thermal repair, which requires long-term repair at high temperature. This method has high energy consumption, slow repair, and performance degradation after repair. As an emerging zero-dimensional nanomaterial in recent years, carbon dots have the advantages of excellent photonic and thermal stability, high water solubility and excellent biocompatibility, and have attracted great research attention in various applications. However, the current research on carbon dots mainly focuses on their fluorescence properties, and relatively little research on their non-radiative relaxation process.
[0004] The present invention uses palm oil fatty acid acrylamide ethyl ester as raw material, hydroxyethyl acrylate and acryloyloxyethyl trimethyl ammonium chloride as copolymer monomers, and prepares palm oil-based elastomers through photocuring technology. In order to solve the problem that the elastomer has poor mechanical properties and cannot be repaired by photocuring, bio-based carbon dots are used to enhance it, so as to give the elastomer photorepair performance. At the same time, due to the presence of polar functional groups on the surface of carbon dots, adding carbon dots as fillers to photocurable resins can form hydrogen bonds between carbon dots and elastomers, thereby enhancing the mechanical properties and toughness of the elastomer. Summary of the invention
[0005] The purpose of the present invention is to make up for the deficiencies in the repair performance of existing bio-based elastomers and provide a photo-repairable bio-based elastomer based on the photothermal effect of carbon dots, which solves the problem that the mechanical properties of current bio-based elastomers are poor and elastomer repair is mainly based on thermal repair. At the same time, the polar groups on the carbon dots form a strong interaction with the polar groups on the elastomer, thereby enhancing the mechanical strength and toughness of the elastomer.
[0006] To achieve the above object, the present invention adopts the following technical solutions: A photo-repairable carbon dot-reinforced bio-based elastomer, which uses palm oil fatty acid acrylamide ethyl ester as a main raw material, bio-based carbon dots as a reinforcement, hydroxyethyl acrylate and acryloyloxyethyl trimethyl ammonium chloride as copolymers, and is prepared by photocuring technology under the action of a photoinitiator; Among them, the amount of each material used, calculated by mass, is: 5.5 parts of palm oil fatty acid acrylamide ethyl ester, 4 parts of hydroxyethyl acrylate, 0.5 parts of acryloyloxyethyltrimethylammonium chloride, 0~0.001 parts of bio-based carbon dots, and 0.2 parts of photoinitiator.
[0007] Furthermore, the bio-based carbon dots are prepared by mixing palmitic acid, p-phenylenediamine, o-phenylenediamine, m-phenylenediamine, 5 mmol / mL sodium hydroxide solution and deionized water, and then subjecting the mixture to a hydrothermal reaction at 210 °C for 8 h, filtering the reaction product with a 0.22 μm filter membrane, dialysis purification and freeze drying.
[0008] Calculated by mass, the amount of each raw material used is 2.5 parts of palmitic acid, 1 part of p-phenylenediamine, 0.1 part of m-phenylenediamine, 0.1 part of o-phenylenediamine, 0.2 part of sodium hydroxide solution, and 100 parts of deionized water.
[0009] Furthermore, the photoinitiator is phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.
[0010] The preparation method of the carbon dot reinforced bio-based elastomer is to mix hydroxyethyl acrylate, acryloyloxyethyl trimethyl ammonium chloride and bio-based carbon dots, stir at room temperature for 1 hour, then add palm oil fatty acid acrylamide ethyl ester and a photoinitiator, stir magnetically at 45°C for 2 hours to make the mixture evenly mixed, and use an ultraviolet lamp with a wavelength of 400 nm for photocuring.
[0011] The beneficial effects of the present invention are: (1) The bio-based carbon dots prepared in the present invention are a type of nanoparticles with a large number of polar functional groups on the surface. They have a good dispersion effect in a polar resin system and a significant photothermal effect.
[0012] (2) The elastomer prepared by the present invention uses renewable palm oil as raw material, is environmentally friendly, and has excellent tensile strength, elongation at break and tensile toughness after being reinforced by carbon dots.
[0013] (3) The preparation of the bio-based photorepairable elastomer of the present invention expands the range of raw material selection and reduces the use of petroleum-based products.
[0014] (4) The elastomer prepared by the present invention has excellent light repair performance. After adding 1‰ carbon dots, it can be completely repaired after 5 hours of light exposure. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 The tensile stress-strain curves of elastomers with different carbon dot contents prepared in the examples.
[0016] Figure 2 This is the stretch recovery curve of the elastomer prepared in Example 3.
[0017] Figure 3 The hydrophobicity of elastomers with different carbon dot contents prepared in the examples.
[0018] Figure 4 This is a graph showing the temperature change of the elastomer prepared in Example 3 with the illumination time.
[0019] Figure 5 This is a graph showing the heating rate of elastomers with different carbon dot contents prepared in the examples under light.
[0020] Figure 6 This is a diagram showing the repair status of elastomers with different carbon dot contents prepared in the examples in a dark environment.
[0021] Figure 7 This is a diagram showing the repair status of elastomers with different carbon dot contents prepared in the examples under the excitation of near-infrared light source.
[0022] Figure 8 The repair rate of the elastomer prepared in Example 3 when stimulated under a near-infrared light source for different periods of time.
[0023] Fig. 9 Experimental picture of photorepair of the elastomer prepared in Example 3. DETAILED DESCRIPTION
[0024] A photorepairable carbon dot-reinforced bio-based elastomer is prepared by mixing 4 parts of hydroxyethyl acrylate, 0.25 parts of acryloyloxyethyl trimethyl ammonium chloride and 0-0.001 parts of bio-based carbon dots by weight, stirring at room temperature for 1 hour, then adding 5.5 parts of palm oil fatty acid acrylamide ethyl ester and 0.2 parts of photoinitiator phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide, stirring magnetically at 45°C for 2 hours to make the mixture evenly mixed, and curing with ultraviolet light with a wavelength of 400 nm for 10 minutes.
[0025] The bio-based carbon dots are prepared by mixing, by weight, 2.5 parts of palmitic acid, 1 part of p-phenylenediamine, 0.1 part of o-phenylenediamine, 0.1 part of m-phenylenediamine, 0.2 parts of 5 mmol / mL sodium hydroxide solution and 100 parts of deionized water, and subjecting the mixture to a hydrothermal reaction at 210° C. for 8 h. The reaction product is filtered through a 0.22 μm filter membrane, purified by dialysis, and freeze-dried.
[0026] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.
[0027] Raw materials: Palm oil (PO) (melting point: 18°C; acid value: 0.16 mg KOH / g) was purchased from Shanghai Dingfen Chemical Technology Co., Ltd., China; N-(2-Hydroxyethyl)acrylamide (>98%), 2,6-dimethylphenol (>99%), sodium chloride (≥99.5%), dichloromethane (≥99.5%), sodium hydroxide (≥96%), palmitic acid (PA), p-phenylenediamine (p-PD), o-phenylenediamine (o-PD), m-phenylenediamine (m-PD), hydroxyethyl acrylate (96%, containing 200-600 ppm MEHQ stabilizer), acryloyloxyethyltrimethylammonium chloride (80 wt%, containing 300 ppm MEHQ stabilizer) and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (photoinitiator TPO819, >97%) were purchased from Aladdin (Shanghai) Reagent Co., Ltd.; tetrahydrofuran (≥99.5%) was purchased from Sinopharm Chemical Reagent Co., Ltd.
[0028] Preparation method of bio-based carbon dots: 2.5 g of palmitic acid, 1 g of p-phenylenediamine, 0.1 g of m-phenylenediamine, 0.1 g of o-phenylenediamine, 0.2 g of sodium hydroxide solution (5 mmol / mL) and 100 g of deionized water are added to a hydrothermal reactor, reacted at 210 °C for 8 h, the reaction product is filtered through a 0.22 μm filter membrane, dialyzed for purification, and freeze-dried to obtain the bio-based carbon dots.
[0029] Preparation method of palm oil fatty acid acrylamide ethyl ester: 150 g palm oil and 150 mL tetrahydrofuran were placed in a three-necked flask, and then 115 g N -hydroxyethyl acrylamide, 0.3 g 2,6-dimethylphenol, and 5 g sodium hydroxide; then, the flask was placed in an oil bath and reacted at 45 °C for 16 h under mechanical stirring (speed 500 r / min), the reaction product was repeatedly purified 3 to 5 times with saturated brine, and purified by rotary evaporation to obtain palm oil fatty acid acrylamide ethyl ester.
[0030] Example 1 The preparation method of the photorepairable carbon dot-reinforced bio-based elastomer is as follows: 4 g of hydroxyethyl acrylate and 0.5 g of acryloyloxyethyl trimethylammonium chloride are mixed and magnetically stirred at room temperature for 1 h, then 5.5 g of palm oil fatty acid acrylamide ethyl ester and 0.2 g of phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide are added, and then magnetically stirred at 45 °C for 2 h to mix evenly, poured into a polytetrafluoroethylene mold, and irradiated under ultraviolet light with a wavelength of 400 nm for 10 min to cure it to obtain the elastomer, which is marked as 0CDE.
[0031] Example 2 The preparation method of photorepairable carbon dot reinforced bio-based elastomer is as follows: 4 g of hydroxyethyl acrylate, 0.5 g of acryloyloxyethyl trimethylammonium chloride and 0.0005 g of bio-based carbon dots are mixed and magnetically stirred at room temperature for 1 h, then 5.5 g of palm oil fatty acid acrylamide ethyl ester and 0.2 g of phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide are added, and then magnetically stirred at 45°C for 2 h to mix evenly, poured into a polytetrafluoroethylene mold, and irradiated under ultraviolet light with a wavelength of 400 nm for 10 min to cure it to obtain the elastomer, wherein the content of bio-based carbon dots accounts for 0.5‰ of the total mass of the elastomer, marked as 0.5CDE.
[0032] Example 3 The preparation method of photorepairable carbon dot reinforced bio-based elastomer is as follows: 4 g of hydroxyethyl acrylate, 0.5 g of acryloyloxyethyl trimethylammonium chloride and 0.001 g of bio-based carbon dots are mixed and magnetically stirred at room temperature for 1 h, then 5.5 g of palm oil fatty acid acrylamide ethyl ester and 0.2 g of phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide are added, and then magnetically stirred at 45°C for 2 h to mix evenly, poured into a polytetrafluoroethylene mold, and irradiated under ultraviolet light with a wavelength of 400 nm for 10 min to cure it to obtain the elastomer, wherein the content of bio-based carbon dots accounts for 1‰ of the total mass of the elastomer, marked as 1CDE.
[0033] Example 4 The preparation method of photorepairable carbon dot reinforced bio-based elastomer is as follows: 4 g of hydroxyethyl acrylate, 0.5 g of acryloyloxyethyl trimethylammonium chloride and 0.0015 g of bio-based carbon dots are mixed and magnetically stirred at room temperature for 1 h, then 5.5 g of palm oil fatty acid acrylamide ethyl ester and 0.2 g of phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide are added, and then magnetically stirred at 45°C for 2 h to mix evenly, poured into a polytetrafluoroethylene mold, and irradiated under ultraviolet light with a wavelength of 400 nm for 10 min to cure it to obtain the elastomer, wherein the content of bio-based carbon dots accounts for 1.5‰ of the total mass of the elastomer, marked as 1.5CDE.
[0034] Elastomer mechanical properties test: According to the embodiment, an elastomer dumbbell-shaped specimen (specifications: 75 mm long, 12 mm wide; 25 mm long in the middle, 4 mm wide, and 1 mm thick) was prepared for tensile performance testing; the tensile performance test was carried out in accordance with GB / T 17037.2‒2020. The tensile performance test was carried out on a microcomputer-controlled electronic universal testing machine at a speed of 50 mm / min.
[0035] Elastomer tensile specimens were subjected to cyclic tensile tests (loading and unloading) at a rate of 50 mm / min at room temperature; in each cycle, the sample was stretched to a strain of 500%.
[0036] Hydrophobic performance test: A 6 μL water droplet was deposited on the sample using a syringe mounted on a liftable square platform; the final image of the liquid-air interface was analyzed by the contact angle system OCA 20 (Dataphysics, Germany) under ambient air pressure and temperature (25°C) and ambient humidity of 50-55%RH.
[0037] Temperature change test: A semiconductor laser (wavelength of 808 nm) was used to irradiate the sample, and a thermal infrared imager was used to record the temperature.
[0038] Photorepair experiment: The tensile specimens were cut with a knife and directly contacted together. A semiconductor laser (wavelength of 808 nm) was used to irradiate the sample. After a certain period of time, the specimens were taken out and their tensile properties were tested.
[0039] Figure 1 The tensile stress-strain curves of the elastomers with different carbon dot contents prepared in the examples are shown in Figure 2. Figure 1 It can be seen that the tensile stresses of 0CDE, 0.5CDE, 1CDE and 1.5CDE are 0.52 MPa, 0.60 MPa, 0.93 MPa and 0.87 MPa, respectively, and the elongations at break are 716%, 667%, 913% and 759%, respectively. It can be seen that the tensile stress and tensile strain of the elastomer first increase and then decrease with the increase of carbon dot content, among which 1CDE has the best performance.
[0040] Figure 2 This is the stretch recovery curve of the elastomer prepared in Example 3. Figure 2 It can be seen that 1CDE elastomer has good recovery: the tensile strain is 500%, and after 5 stretching cycles, the tensile stress is 0.23 MPa, which is 79.3% of the initial strength; the tensile toughness recovers to 0.47 MJ / m³, which is 52.7% of the initial toughness, proving that it has good recovery ability.
[0041] Figure 3 The hydrophobicity of the elastomers with different carbon dot contents prepared in the examples. Figure 3 It can be seen that the water contact angles of 0CDE, 0.5CDE, 1CDE and 1.5CDE are 110.5°, 124.5°, 130.4° and 129.3°, respectively, proving that they have good hydrophobic properties.
[0042] Figure 4The temperature change of the elastomer prepared in Example 3 with the light exposure time is shown in FIG. Figure 4 It can be seen that the elastomer 1CDE heats up rapidly under near-infrared light irradiation and reaches equilibrium after 10 min, with a temperature of about 100°C.
[0043] Figure 5 The figure is a graph showing the heating rate of the elastomers with different carbon dot contents prepared in the examples under light. Figure 5 It can be seen that under near-infrared light irradiation, the temperature of the elastomer increases significantly with the increase of carbon dot content.
[0044] Figure 6 This is a diagram showing the repair of elastomers with different carbon dot contents prepared in the examples in a dark environment. Figure 6 It can be seen that the repairability of elastomers with different carbon dot contents in a dark environment is poor. Specifically, the tensile stresses of 0CDE, 0.5CDE, 1CDE and 1.5CDE after repair are only 0.05 MPa, 0.08 MPa, 0.12 MPa and 0.09 MPa, respectively.
[0045] Figure 7 The figure is a diagram showing the repair of elastomers with different carbon dot contents prepared in the examples under near-infrared light excitation. Figure 7 It can be seen that the addition of carbon dots makes the elastomer have better repairability under near-infrared light source excitation. Specifically, the tensile stresses of 0CDE, 0.5CDE, 1CDE and 1.5CDE after repair are 0.13 MPa, 0.34 MPa, 0.73 MPa and 0.69 MPa, respectively. Among them, the tensile stress of 1CDE is 78.5% of the original strength.
[0046] Figure 8 The repair rate of the elastomer prepared in Example 3 under near-infrared light source at different times. Figure 8 It can be seen that with the increase of the excitation time of the near-infrared light source, the repair performance of the elastomer gradually increases.
[0047] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A photorepairable carbon dot-reinforced bio-based elastomer, characterized in that: The elastomer is prepared by using palm oil fatty acid acrylamide ethyl ester as a main raw material, bio-based carbon dots as a reinforcement, hydroxyethyl acrylate and acryloyloxyethyl trimethyl ammonium chloride as copolymer monomers through photocuring technology under the action of a photoinitiator.
2. The carbon dot reinforced bio-based elastomer according to claim 1, characterized in that: The amount of each material used is calculated by mass: 5.5 parts of palm oil fatty acid acrylamide ethyl ester, 4 parts of hydroxyethyl acrylate, 0.5 parts of acryloyloxyethyl trimethyl ammonium chloride, 0-0.001 parts of bio-based carbon dots, and 0.2 parts of photoinitiator.
3. The carbon dot reinforced bio-based elastomer according to claim 1 or 2, characterized in that: The bio-based carbon dots are prepared by mixing palmitic acid, p-phenylenediamine, o-phenylenediamine, m-phenylenediamine, 5 mmol / mL sodium hydroxide solution and deionized water, and subjecting the mixture to a hydrothermal reaction at 210° C. for 8 h. The reaction product is filtered through a 0.22 μm filter membrane, purified by dialysis, and freeze-dried.
4. The carbon dot reinforced bio-based elastomer according to claim 3, characterized in that: Calculated by mass, the amount of each raw material used is 2.5 parts of palmitic acid, 1 part of p-phenylenediamine, 0.1 part of m-phenylenediamine, 0.1 part of o-phenylenediamine, 0.2 part of sodium hydroxide solution, and 100 parts of deionized water.
5. The carbon dot reinforced bio-based elastomer according to claim 1 or 2, characterized in that: The photoinitiator is phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.
6. The carbon dot reinforced bio-based elastomer according to claim 1, characterized in that: Its preparation is to mix hydroxyethyl acrylate, acryloyloxyethyl trimethyl ammonium chloride and bio-based carbon dots, stir at room temperature for 1 hour, then add palm oil fatty acid acrylamide ethyl ester and photoinitiator, magnetically stir at 45 ° C for 2 hours to make the mixture evenly mixed, and use ultraviolet lamp with a wavelength of 400 nm for photocuring.